Sistem Pendukung Keputusan Penentuan Kegiatan Ekstrakurikuler Sekolah Terbaik Menerapkan Metode TOPSIS dan ROC - Adam Huda Nugraha; Imam Purwanto; Agus Turiyono (Bulletin of Computer Science Research, 2025)
Extracurricular activities (ekskul) are one of the additional components in the school education system, carried out outside of curriculum learning hours. The purpose of extracurricular activities is to hone students' abilities, add insight, improve skills, and arouse the enthusiasm of students through non-academic activities. However, there are still many students who are reluctant to join extracurricular activities, perhaps due to a lack of information or interest in the types of activities offered. In this research, a Decision Support System is introduced to help determine the best school extracurricular activities. This system is designed to provide recommendations for extracurricular activities that match the interests and potential of students. The method used in the development of this system is the AHP (Analytic Hierarchy Process) method to determine the priority of extracurricular activities that best fit the criteria that have been set. The results of this study show that the "A2 Martial Arts" activity gets the highest score of 0.7909 and is ranked first as the best extracurricular activity. This recommendation is expected to increase student participation in extracurricular activities and support the development of the potential and skills of students at school.